Private Equity, Investment and Financial Constraints – Firm-Level Evidence for France and the United Kingdom - Dirk Engel; Joel Stiebale (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The welfare effects of private equity transactions are debated controversially. We analyze the impact of expansion financing and buyouts by private equity investors on investment of portfolio firms in the UK and France - two countries with different financial systems. Unobserved heterogeneity and the endogeneity of private equity transactions financed by venture capital companies are addressed using dynamic panel data techniques. In both countries we find that portfolio firms display higher investment levels and a lower dependence on internal funds after expansion financing. Buyouts financed by venture capital companies are neither associated with a decrease in investment spending nor with an increase in the dependence on internal finance. In contrary, private equity based buyouts in the UK outperform non-private equity backed British firms in terms of both indicators. Contrasting the notion of several policy makers,we cannot detect that private equity based buyout financing yields higher financial constraints on average.
Keywords: G32; D92; G23; 330; Investment; financial constraints; private equity; Private Equity; Übernahme; Unternehmensentwicklung; Investition; Verschuldungsrestriktion; Vergleich; Finanzsektor; Großbritannien; Frankreich